Does Religion Affect Capital Structure in Indonesia? - Rahim, Rida; Utama, Cynthia Afriani; Rokhim, Rofikoh (Pertanika Journal of Social Sciences & Humanities)
The purpose of this study is to analyse the influence of the religion and religious values of Chief Executive Officers (CEOs) on capital structure in public companies in Indonesia. The religious values embraced by CEOs are reflected in their involvement in fraud cases and the frequency of their attendance at board meetings. The study used a sample of 231 companies (1,386 observations) over the period 2010-2015. It was found that if firms had a Christian CEO this would have a significant impact on capital structure due to the higher debt levels, compared to CEOs of other religions. Conversely, Muslim CEOs had an insignificant impact on capital structure. Similarly, CEOs who were involved in fraud cases had more debt than those not involved in such cases. CEO attendance at board meetings also had a significant positive impact on corporate debt level.